Exploring Western Ghats microbial diversity for antagonistic microorganisms against fungal phytopathogens of pepper and chickpea - B.N. RAMKUMAR; K.M. NAMPOOTHIRI; U. SHEEBA; P. JAYACHANDRAN; N.S. SREESHMA; S.M. SNEHA; K.S. Meenakumari; P. Sivaprasad (Journal of BioScience and Biotechnology, 2015)
Newly isolated microbial cultures from Western Ghat soil samples of Kerala region in India were screened for antagonistic activity by well diffusion and dual culture plating against Phytophthora capsici and Rhizoctonia solani, infecting pepper and chickpea, respectively. Bioactive samples were made by varying solvent extraction of the culture broths of the potent isolates belongs to Actinomycetes, Pseudomonas, Bacillus and Trichoderma. The efficacy of the isolates to produce other potent antifungal metabolites such as cell wall degrading enzymes, HCN and volatile compounds were also checked. Treatment with antagonistic isolates in vivo under greenhouse conditions revealed significant reduction of the disease intensity of foot rot disease of black pepper and collar rot of chick pea.